An encapsulated packet-selection routing for network on chip. (February 2019) - Liu, Lu; Ma, Rui; Zhu, Zhangming
Abstract: Enhanced performance and reduced overhead are critical to Network-on-Chip (NoC) design. Locally congestion-aware (LCA) routing decisions have been proved as effective solutions. In this paper, we present an encapsulated packet-selection routing (EnPSR) that provides admissible output channels with available adjacent VCs at packet injection stage, which selects injected packets for available output channels; conventional routing computation units in EnPSR router can be eliminated. Evaluation results show that the proposed EnPSR yields a reduced average packet latency by 12.1% and an improved throughput by 3.6%, the area and power costs of EnPSR are reduced by 11.3% and 9.6% respectively.